2014
DOI: 10.1371/journal.pone.0111399
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Validation for Quantitative RT-PCR during Biotic and Abiotic Stresses in Vitis vinifera

Abstract: Grapevine is one of the most cultivated fruit crop worldwide with Vitis vinifera being the species with the highest economical importance. Being highly susceptible to fungal pathogens and increasingly affected by environmental factors, it has become an important agricultural research area, where gene expression analysis plays a fundamental role. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) is currently amongst the most powerful techniques to perform gene expression studies. Neverthele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 53 publications
4
28
0
Order By: Relevance
“…These variations are caused by the differences in RNA quality, reverse transcription efficiency, and PCR efficiency. (Chandna et al, 2012), Arachis hypogea L. (Reddy et al, 2013), Vitis vinifera L. (Borges et al, 2014), Pennisetum glaucum (L.) R. Br. Such a method involves the use of a reference gene(s).…”
Section: Identification Of Reference Genes For Qrt-pcr Gene Expressiomentioning
confidence: 99%
See 1 more Smart Citation
“…These variations are caused by the differences in RNA quality, reverse transcription efficiency, and PCR efficiency. (Chandna et al, 2012), Arachis hypogea L. (Reddy et al, 2013), Vitis vinifera L. (Borges et al, 2014), Pennisetum glaucum (L.) R. Br. Such a method involves the use of a reference gene(s).…”
Section: Identification Of Reference Genes For Qrt-pcr Gene Expressiomentioning
confidence: 99%
“…, Zea mays L. (Manoli et al, 2012), Brassica juncea (L.) Czern. (Chandna et al, 2012), Arachis hypogea L. (Reddy et al, 2013), Vitis vinifera L. (Borges et al, 2014), Pennisetum glaucum (L.) R. Br. (Reddy et al, 2015), and Apium graveolens L. (Li et al, 2016), have shown that the expression of the HKGs is not as stable as it was generally assumed.…”
mentioning
confidence: 99%
“…Then, real-time PCR was carried out to detect gene relative transcriptional expression abundance according to the method of Borges et al [2]. cDNA was prepared using PrimeScript™ RT reagent Kit (Takara, Dalian, China) under instructions.…”
Section: Gene Transcription Expression Analysis Of Key Enzymes By Reamentioning
confidence: 99%
“…Suitable reference genes for each experimental set should be identified independently. In grapevine, reference genes have been evaluated for different varieties [31], developmental stages [14], and physiological conditions [4], such as biotic and abiotic stress. This need to optimize reference genes for different conditions arises in studies of other plants, such as rice [18,30,45], potato [27,40], apple [5,21], and strawberry [12].…”
Section: Introductionmentioning
confidence: 99%